Allocation of food allergy responsibilities and its correlates for children and adolescents. (June 2015) - Annunziato, Rachel A; Rubes, Melissa; Ambrose, Michael; Caso, Nicole; Dillon, Matthew; Sicherer, Scott H; Shemesh, Eyal
This study examined the degree to which children and adolescents with food allergy accept responsibility for their own care, and the extent to which greater self-management is associated with past history of a life-threatening allergic reaction or anxiety. For children ( n = 190), caregiver and patient report of self-management was consistent, but agreement was poor for adolescent dyads ( n = 59). History of a life-threatening allergic reaction was associated with greater self-management for children only, while among adolescents, it was associated with greater anxiety. Given that shifting to self-management may be challenging, discussion and preparation about this process is warranted.